MANAGEMENT OF HAPANASAN TOURISM OBJECT IN THE VILLAGE OF RAMBAH TENGAH HULU RAMBAH DISTRICT ROKAN HULU REGENCY - Marini Yunita; Siti Sofro Sidiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Hapanasan hot spring tourism object is one of the leading tourist in the Rokan Hulu, the location of Hapanasan hot water is in the village of Rambah Tengah Hulu. An exotic tourist location with a natural atmosphere that is still very pronounced and has hot springs as a volcanic post. This study aims to (1) ind out how the management of Hapanasan hot water tourism objects in the future (2) to find out what are the management constraints in Hapanasan hot water attractions. Management has 4 functions of planning, organization, actuating, controlling. This study used a qualitative method. The data were obtained by colleting field data with a qualitative approach. This research is a descriptive study using the research subject of Hapanasan hot water tourism object management in the village of Rambah Tengah Hulu Rambah subdistrict Rokan Hulu Regency. The data collection technique was done by means of interviews, observation, and documentation. The analysis used in this research is data reduction, drawing conclusions and data presentation. The result of this study indicate that this hot spring tourist attraction has management as a health tourism planning process and will build UKM. Regarding organizing, it includes the management of the tourism and culture office of the Rokan Hulu District and Pokdarwis (travel conscious) Regarding the implementation of duties divided by the tourism and culture of to manage, promote, care for and protect the Hapanasan area. Regarding the supervision carried out by the tourism and culture office of the Rokan Hulu Regency. Keywords : Management, Tourist Attraction, Hapanasan